The economic empowerment of women in Colombia and Argentina: an analysis of human rights and public policy - Mora Cuervo, Ruth Astrid (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The reduction of inequalities and gaps between men and women has been evident in recent decades, particularly since the recognition of women's human rights and the progress of the Regional Gender Agenda in Latin America. However, at the economic level there is still inequality of income and opportunities, derived from the lack of knowledge of the economic role they play. The objective of this work is to analyze the guarantee of human rights that the public policies of equity/gender equality of Colombia and Argentina establish to achieve their economic empowerment, for which a qualitative and case study approach was adopted, with the purpose of applying a normative evaluation of both policies and their contrast with recent figures on income, unpaid work and occupations of women compared to men. It is found that both policies comply with most of the minimum contents of women's human rights regarding their political autonomy; however, the figures for each country show that equality has not yet been achieved in economic matters. It is concluded that countries can carry out normative evaluations of their policies in order to incorporate new frameworks for action in the region.